2005
DOI: 10.1007/s00383-005-1573-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gene targeting in human Hepatoblastoma

Abstract: Poor treatment results in advanced hepatoblastoma (HB) made alternative treatment approaches desirable. Gene-directed tumor therapy is increasingly investigated in different malignancies. The aim of this study was to analyze possible alternatives of gene transfer into HB cells and to study therapeutic applications based on different strategies. Liposomal transfection of HB cells was assessed using liver-specific promoters, and adenovirus and Sendai virus transductions were performed in vitro. Transfer efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Whereas Feng postulated Bcl-2 as potential therapy target of the HCC cell line HepG2, Ikeguchi et al did not find a clinical importance of the Bcl-2/Bax ratio analyzing 53 patients with HCC [13,34]. Our own preliminary data indicated the possibility of improved treatment outcomes in HB through Bcl-2 knockdown [5].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Whereas Feng postulated Bcl-2 as potential therapy target of the HCC cell line HepG2, Ikeguchi et al did not find a clinical importance of the Bcl-2/Bax ratio analyzing 53 patients with HCC [13,34]. Our own preliminary data indicated the possibility of improved treatment outcomes in HB through Bcl-2 knockdown [5].…”
Section: Discussionmentioning
confidence: 86%
“…The technique of RNA interference using siRNA has been established as an effective treatment approach against various malignancies including liver tumors in adults [5,6,24,39]. Although there exist alternative methods of cell transfection [40,41], we found the siRNA approach being effective and reliable for the intended purpose.…”
Section: Discussionmentioning
confidence: 99%
“…As a general rule, the viral vectors are known to display higher transfer rates of therapeutic genes than lipofectants, as we recently confirmed for the HB gene transfer in a pilot study using adenoviral and Sendai viral vectors [26].…”
Section: Discussionmentioning
confidence: 86%
“…HB were found to express differing transcriptional activities of synthetic liver-specific transcriptional control unit constructs according to the histological background [42]. These findings indicate the necessity for a purposeful selection of HB active promoter cassettes prior to their employment in future therapeutic approaches of HB treatment.…”
Section: Gene Transfer Systems For Hepatoblastomamentioning
confidence: 98%
“…Initial studies on HB demonstrated the tumors' susceptibility to gene transfer, clone development and therapeutic approaches using liposomal transfection as well as viral vectors [41,42]. Systematic analyses of gene transfer systems revealed liposomal transfection using either the multi-component lipid based FuGENE 6™ transfection reagent (Roche Diagnostics), or the cationic lipid reagent Lipofectamine™ 2000 (Invitrogen) as advantageous in terms of handling and safety.…”
Section: Gene Transfer Systems For Hepatoblastomamentioning
confidence: 98%